Analysis of students' perceptions on the Freedom of Learning - Independent Campus (MBKM) program at Chemistry study program of Ma Chung University - Yuniati, Yuyun; Wilujeng, Lilis Lestari (Graduate School, Universitas Negeri Yogyakarta in cooperation with Himpunan Evaluasi Pendidikan Indonesia (HEPI) Yogyakarta, 2023)
Considering that Indonesian education has gone through such a long journey from 1922 to 2022 now, it is necessary to have an educational program that is able to meet the demands of workers' needs in this era of globalization. In the end, the Directorate General of Higher Education, Research, and Technology designed an education policy system in the realm of higher education, namely